Analisis Kesiapan Guru Dalam Melaksanakan Pembelajaran Kurikulum Merdeka Belajar Di SD Negeri 122 Palembang - Mia Marsella Pratiwi; Yasir Arafat; Murjainah Murjainah (Journal on Education, 2023)
The most important learning is the curriculum, because the things in the curriculum are in accordance with the needs in the field. The curriculum is a set of plans and arrangements regarding objectives, content, learning materials and methods used as guidelines for implementing learning activities to be achieved. The purpose of this study was to determine the readiness in implementing the independent learning curriculum at SD Negeri 122 Palembang. This research method uses a qualitative descriptive method. The subjects in teachers, principals and vice principals of Palembang 122 Public Elementary School. Data collection techniques used are in the form of observation, interviews and documentation. The results of this study indicate that the readiness teachers in implementing the independent learning curriculum is ready and understands and is in accordance with the indicators of teacher readiness in the independent learning curriculum which is the reference for researchers in this study. Indicators of teacher readiness in the independent learning curriculum which are the reference for researchers are readiness in understanding the structure of the independent curriculum, readiness of lesson plans, readiness of the learning process, readiness of teaching modules, learning assessment. are ready to carry out independent learning curriculum learning.